Magnesium Lithospermate B Downregulates the Levels of Blood Pressure, Inflammation, and Oxidative Stress in Pregnant Rats with Hypertension - Kaixiang Xu; Xiaohong Zang; Mian Peng; Qian Zhao; Binbin Lin (International Journal of Hypertension)
Background. Magnesium lithospermate B (MLB) was shown to suppress oxidative stress and reduce hypertension, but the role of MLB in pregnancy-induced hypertension (PIH) remains unknown. The objective of this study was to demonstrate the effects of MLB on rats with PIH. Methods. A total of 40 pregnant SD rats were selected, and 30 rats were orally given NG-nitro-L-arginine methyl ester (L-NAME, 60 mg/kg/day) to establish PIH rat models. Rats were equally divided into four groups: control, PIH, 5 mg/kg MLB, and 10 mg/kg MLB. MLB was consecutively administered into PIH rats for one week. The effects of MLB on mean arterial blood pressure (MAP), urine protein level, inflammation, and oxidative stress together with angiogenesis were analyzed. Results. MLB prevented the elevation in MAP and urine protein levels induced by L-NAME. The activities of inflammatory cytokines were highly increased in serum and placental tissues of PIH rats, while cotreatment with MLB partially reversed the activities of these cytokines. MLB also recovered the expression of reactive oxygen species (ROS) in plasma of PIH rats together with levels of oxidative stress and antioxidant capacity in the placenta of PIH rats. The decreased expressions of vascular endothelial growth factor (VEGF), endothelial nitric oxide synthase (eNOS), and NO observed in PIH rats were increased by MLB. In addition, 10 mg/kg MLB exhibited higher protective effects as compared to lower doses of 5 mg/kg. Conclusion. This study demonstrated that pretreatment with MLB decreased MAP, inflammation, and oxidative stress in rats with gestational hypertension.